Gender Roles, Family Models and Community-Building Processes in Poblenou - Grassi, Silvia (Rassegna Iberistica, 2018)
This article explores connections between construction of gender roles, family models and community-building processes in soap opera narratives. The underlying research hypothesis maintains that construction of gender roles and family models in soap operas influences values around which a sense of community is constructed. Using textual analysis as methodology and an intercultural approach, this study compares and contrasts British and American soap operas. This approach allows to set out two contrasting models and investigate whether and to what extent Catalan soap operas adhere to one of them by proposing an original analysis of selected characters and storylines from a corpus of Catalan drama serials. This article also queries in which ways Catalonia’s situation as a stateless nation influences a sense of community construction in Catalan soap operas.